A New Kind of GeoInformatics Built on Living Structure and on the Third View of Space - Bin JIANG (Journal of Geodesy and Geoinformation Science, 2022)
The third view of space states that space is neither lifeless nor neutral, but a living structure capable of being more living or less living. The living structure is defined as a physical and mathematical structure or simply characterized by the recurring notion (or the inherent hierarchy) of far more small substructures than large ones. The more substructures the more living, and the higher hierarchy of the substructures the more living. This paper seeks to lay out a new kind of GeoInformatics on the notion of living structure and on the third view of space. The new GeoInformatics aims not only to better understand the forms and processes of everyday space but also-maybe more importantly-to make the space or the Earth’s surface living or more living. We introduce two fundamental laws of living structure: Tobler’s law on spatial dependence or homogeneity and scaling law on spatial interdependence or heterogeneity. We further argue that these two laws favor statistics over exactitude, because the statistics tend to make a structure more living than the exactitude. We present the concept of living structure through some working examples and make it clear how a living structure differs from a non-living or less-living structure. In order to make a structure or space living or more living, we introduce two design principles-differentiation and adaptation-using two paintings and two city plans as working examples. The new GeoInformatics is a science of living structure, dealing with a wide range of scales of the everyday space, from the smallest scale of ornaments on walls to the scale of the entire Earth’s surface.